Agama Sebagai Konstruksi Sosial dan Wahyu Ilahi: Analisis Komparatif Perspektif Barat dan Islam - Ash Shifa Annur; Miftahul Jannah (Jurnal Ilmiah Guru Madrasah, 2025)
Religion has been extensively examined within Western sociological traditions, predominantly interpreting it as a socio-historical construct. In contrast, Islamic thought conceptualizes religion (ad-dīn) as divinely revealed, governing all human dimensions. Despite abundant literature, comparative studies examining these paradigms through epistemological frameworks remain limited. This study addresses this gap through comparative-critical analysis of Western and Islamic perspectives on religion. Using qualitative library research with thematic analysis, this article examines classical Western thinkers (Comte, Durkheim, Marx, Freud, Weber) alongside Islamic scholars and Qur'anic interpretations. Findings reveal fundamental epistemological divergence: Western perspectives view religion as socio-historical construct subject to change, while Islam positions religion as fixed divine revelation whose development occurs at interpretive, not substantive, levels. Western evolutionary frameworks cannot fully apply to Islamic religious dynamics without epistemological recalibration. This study contributes to comparative religious studies by clarifying conceptual boundaries between sociological and theological approaches, with implications for interfaith dialogue and contemporary Islamic scholarship.